Hosting an eConference: Interactive video conference grand rounds between two institutions - Jeffrey Rixe; Kiersten Carter; Alexander Y Sheng; Jordan Spector; Katie Doering; Jeffrey Chien; Nikita Joshi (eScholarship Publishing, University of California, 2018)
Audience: The eConference is an interactive video conference grand rounds innovation to augment the didactic curriculum provided for medical students, interns, residents, fellows, and attending physicians. Introduction: Formal education during emergency medicine (EM) training has historically emphasized aspects of humanism and constructivism; the former through self-directed reading in books and journals, the latter through the content and discussion during resident didactics.1 However, some studies suggest that the current generation of EM learners are increasingly using digital and internet technologies to connect with online peer networks, a phenomenon known as connectivism.2 As such, contemporary EM learners are increasingly utilizing social media and Free Open Access Medical Education (FOAM) to supplement traditional learning resources. The eConference was developed to be an interactive, virtual grand rounds that marries the merits of constructivism with connectivism; a new format of EM didactics that goes beyond the "typical lecture" model to incorporate the changing landscape in technology and medical education by combining classroom teaching at multiple institutions alongside digital learning tools. This manuscript outlines how to plan and execute a joint video conference with another institution. Objectives: Our objectives were to create and implement a novel virtual conference format through the integration of social media tools which allows for interdisciplinary and multi-site participation to enhance EM resident education. We wish to outline the steps required to reproduce this innovative session and share lessons learned. Conclusion: We designed and executed a multi-centered, novel form of virtual conference into the EM residency curriculum at two participating institutions. The virtual conference took place during a routine conference day for both programs, an hour in duration. The format utilized a hybrid of live and virtual lectures based upon a clinical case presentation that was broadcast to and from both institutions, utilizing Google HangoutsTM and TwitterTM. Senior house staff, EM faculty and subspecialty content experts combined to present the case and guide the cross-institutional discussion.